Respuesta :
Comparing the functions, it is found that:
- For the first two functions, a input of x = 0 produces the same output values.
- For the last two functions, a input of x = 3 produces the same output values.
---------------------------------------------------
First two functions:
[tex]f(x) = -\frac{2}{3}(x+1)[/tex]
[tex]g(x) = \frac{1}{3}(x-2}[/tex]
The outputs are equal when:
[tex]f(x) = g(x)[/tex]
[tex]-\frac{2}{3}(x+1) = \frac{1}{3}(x-2}[/tex]
[tex]-\frac{2}{3}x - \frac{2}{3} = \frac{1}{3}x - \frac{2}{3}[/tex]
[tex]-\frac{2}{3}x - \frac{1}{3}x = -\frac{2}{3} + \frac{2}{3}[/tex]
[tex]-x = 0[/tex]
[tex]x = 0[/tex]
For the first two functions, a input of x = 0 produces the same output values.
---------------------------------------------------
Last two functions:
- f(x) goes through: (-3,3), (0,1), (3,-1)
- g(x) goes through: (-3,-3), (0,-2), (3,-1)
For the two functions, when the input is [tex]x = 3[/tex], the output is [tex]y = 1[/tex]. Thus.
For the last two functions, a input of x = 3 produces the same output values.
A similar problem is given at https://brainly.com/question/13774366